Get to the heart of pediatric kidney transplant recipients: Evaluation of left- and right ventricular mechanics by three-dimensional echocardiography - Ladányi, Zsuzsanna; Bárczi, Adrienn; Fábián, Alexandra; Ujvári, Adrienn; Cseprekál, Orsolya; Kis, Éva; Reusz, György Sándor; Kovács, Attila; Merkely, Béla; Lakatos, Bálint Károly (Frontiers in Cardiovascular Medicine, 2023)
Background: Kidney transplantation (KTX) markedly improves prognosis in pediatric patients with end-stage kidney failure. Still, these patients have an increased risk of developing cardiovascular disease due to multiple risk factors. Three-dimensional (3D) echocardiography allows detailed assessment of the heart and may unveil distinct functional and morphological changes in this patient population that would be undetectable by conventional methods. Accordingly, our aim was to examine left- (LV) and right ventricular (RV) morphology and mechanics in pediatric KTX patients using 3D echocardiography. Materials and Methods: Pediatric KTX recipients (n=74) with median age 20 [14-26] years at study enrollment (43% female), were compared to 74 age and gender-matched controls. Detailed patient history was obtained. After conventional echocardiographic protocol, 3D loops were acquired and measured using commercially available software and the ReVISION Method. We measured LV and RV end-diastolic volumes indexed to body surface area (EDVi), ejection fraction (EF), and 3D LV and RV global longitudinal (GLS) and circumferential strains (GCS). Results: Both LVEDVi (67±17 vs. 61±9 mL/m2; p<0.01) and RVEDVi (68±18 vs. 61±11 mL/m2; p<0.01) were significantly higher in KTX patients. LVEF was comparable between the two groups (60±6 vs. 61±4 %; p=NS), however, LVGLS was significantly lower (-20.5±3.0 vs. -22.0±1.7 %; p<0.001), while LVGCS did not differ (-29.7±4.3 vs. -28.6±10.0 %; p=NS). RVEF (59±6 vs. 61±4 %; p<0.05) and RVGLS (-22.8±3.7 vs. -24.1±3.3 %; p<0.05) were significantly lower, however, RVGCS was comparable between the two groups (-23.7±4.5 vs. -24.8±4.4 %; p=NS). In patients requiring dialysis prior to KTX (n=64, 86 %) RVGCS showed correlation with the length of dialysis (r=0.32, p<0.05). Conclusions: Pediatric KTX patients demonstrate changes in both LV and RV morphology and mechanics. Moreover, the length of dialysis correlated with the contraction pattern of the right ventricle.